Challenges in sharing information effectively: examples from command and control - Diane H. Sonnenwald (Information Research: An International Electronic Journal)
The goal of information sharing is to change a person's image of the world and to develop a shared working understanding. It is an essential component of collaboration. This paper examines barriers to sharing information effectively in dynamic group work situations.Three types of battlefield training simulations were observed and open-ended interviews with military personnel were conducted. Observation notes and interview transcripts were analysed to identify incidents when group members erroneously believed they had shared information effectively and were collaborating successfully, i.e., a deceptively false shared understanding had emerged. These incidents were analysed to discover what led to these unsuspected breakdowns in information sharing. Results. Unsuspected breakdowns in information sharing emerged when: differences in implementations of shared symbols were not recognized; implications of relevant information were not shared; differences in the role and expression of emotions when sharing information was not understood; and, the need to re-establish trust was not recognized. Conclusion. The challenges in information sharing identified here may extend to other high stress, unique and complex situations, such as natural disasters. Recommendations for more effective information behavior techniques in dynamic group work situations are presented.